Evaluation of enterprise performance based on FLI-GA model - Shouyi Zhang; Xiaomin Zhu; Jiandong Geng; Runtong Zhang (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: There are many kinds of methods to evaluate the performance of enterprise, but they still have some distinct shortcomings. In order to achieve a better evaluation result, we put forward a new model named FLI-GA (Fuzzy logic inference & Genetic algorithm). Approach: This model, mainly based on the fuzzy logic inference method, uses fuzzy rule-based system (FRBS) to avoid the drawbacks of FRBS. Genetic algorithm is applied in this model. Findings: FLI-GA model can be used to evaluate certain enterprise performance, and its evaluation results are more accurate than fuzzy logic inference method. Originality: This model combines the genetic algorithm with the unclear reasoning methods so as to make the appraisal results more reasonable and more satisfying.
Keywords: 650; FLI-GA model; performance evaluation; genetic algorithm